Metabolic Engineering of Non-carotenoid-Producing Yeast Yarrowia lipolytica for the Biosynthesis of Zeaxanthin - Xie, Yuxiao; Chen, Shulin; Xiong, Xiaochao (Frontiers in Microbiology, 2021)
Zeaxanthin is vital to human health thus its production has received great attention, and it is also an essential precursor for the biosynthesis of other critical carotenoid compounds such as astaxanthin and crocetin. Yarrowia lipolytica is one of the most intensively studied non-conventional yeasts and has been genetically engineered as a cell factory to produce carotenoids such as lycopene, β-carotene, and astaxanthin. However, zeaxanthin production by Y. lipolytica has not been well investigated. To fill this gap, β-carotene biosynthesis pathway has been first constructed in this study by expression of the key genes, including crtE, crtB, crtI, and carRP. Three crtZ genes encoding β-carotene hydroxylase from different organisms were individually introduced into β-carotene-producing Y. lipolytica to evaluate their performance for producing zeaxanthin. Expression of crtZ from Pantoea ananatis (formerly Erwinia uredovora, Eu-CrtZ) resulted in the highest zeaxanthin titer and content on the basis of dry cell weight (DCW). After verifying the function of Eu-CrtZ for producing zeaxanthin, high-copy-number integration into the ribosomal DNA of Y. lipolytica led to a 4.02-fold increase in the titer of zeaxanthin and a 721% increase in the content of zeaxanthin. The highest zeaxanthin titer achieved 21.98 ± 1.80 mg/L by the strain grown on yeast extract peptone dextrose (YPD) rich medium. In contrast, the highest content of DCW reached 3.20 ± 0.11 mg/g by using a synthetic yeast nitrogen base (YNB) medium to culture the cells. Cell growth, glucose consumption, carotenoid profiles, and by-product citric acid secretion have been investigated during zeaxanthin production. The results demonstrated the potential of a cell factory for zeaxanthin biosynthesis and opened up an avenue to engineer this host for the overproduction of carotenoid compounds.